New and interesting moths from the East Palaearctic (Lepidoptera: Tineidae). Contributions to the knowledge East Palaearctic insects (11). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 2000)
The results of the study of unidentified material from the Russian Far East and from Japan are presented. The following new species are described: Dryadaula ussurica, D. multifurcata, Nemapogon robusta, N. echinata, N. agnathosella, Agnathosia chasanica, Eudarcia ronata, E. sinjovi, E. dentata, Crypsithyris saigusai, Monopis zagulajevi. Morophaga parabucephala Ponomarenko & Park, 1996 is placed in the synonymy of M. bucephala (Snellen, 1884). The species orientanus Ponomarenko & Park, 1996, described in the genus Ceratuncus, is attributed to the genus Triaxomasia, the species orbiculidomus (Sakai & Saigusa, 1999) described in the genus Obesoceras, is attributed to the genus Eudarcia (new combination). A catalogue of the species from the Russian Far East and from Japan is given. Nomenclatural Actschasanica Gaedkie, 2000 (Agnathosia), spec. n.saigusai Gaedike, 2000 (Crypsithyris), spec. n.multifurcata Gaedike, 2000 (Dryadaula), spec. n.ussurica Gaedike, 2000 (Dryadaula), spec. n.dentata Gaedike, 2000 (Eudarcia), spec. n.orbiculidomus (Sakai & Saigusa, 1999) (Eudarcia), comb. n. hitherto obesoceras orbiculidomussinjovi Gaedike, 2000 (Eudarcia), spec. n.ornata Gaedike, 2000 (Eudarica), spec. n.zagulajevi Gaedike, 2000 (Monopis), spec. n.parabucephala Ponomarenko & Park, 1996 (Morophaga), syn. n. of Morophaga bucephala (Snellen, 1884)agnathosella Gaedike, 2000 (Nemapogon), spec. n.echinata Gaedike, 2000 (Nemapogon), spec. nov.robusta Gaedike, 2000 (Nemapogon), spec. n.orientanus (Ponomarenko & Park, 1996) (Triaxomasia), comb. n. hitherto Ceratuncus orientanus